ASAP CAIR DARI LIMBAH KULIT MANGROVE Avicennia alba UNTUK PENGAWETAN BAKSO IKAN (LIQUID SMOKE FROM MANGROVE SKIN WASTE Avicennia alba FOR THE PRESERVATION OF FISH BALLS) - Anthoni Batahan Aritonang; Fransiska M Wenisda; Mega S Sofiana (Indonesian Journal of Pure and Applied Chemistry, 2020)
Liquid smoke has been successful pabricated from mangrove Avicennia alba shell by pyrolysis method at a temperature of 400℃ for 3 hours. Liquid smoke was purified by adsorption using activated kaolinite as adsorbent.  The test results showed that activated kaolinite could bring down the rancidness to become odorless and the color of liquid smoke from dark chocolate to gray colour. The composition of the liquid smoke compound was determined by using the Gass Chromatography-Mass  Spectrophotometer (GC-MS) consists of 2-propanone (CAS) acetone 25.79% and furan, tetrahydro- of 10.37% and carbamic acid, monoammonium salt (CAS) ammonium carbamate of 58.46% . The LC50 value of pure liquid smoke ranging from 1000 ppm is an indication that it is not toxic and safe to use for food preservation.  Activity test against the inhibition of microbial growth in fish meatballs, showed that ability. The higher the concentration of liquid smoke, the better the inhibition of microbial growth. Based on the results, it can be concluded that the liquid smoke produced from mangrove Avicennia alba shell purified by the activated kaolinite is very promising as a foodstuffs preservative